The usability of Brazilian government open data portals: ensuring data quality - Francisca Tejedo-Romero; Joaquim Filipe Ferraz Esteves Araujo; Marcelo Jesus Gonçalves Ribeiro (Humanities & Social Sciences Communications)
Abstract Recent decades have witnessed a massive movement supported by many governments to make an effort to promote transparency through the dissemination of data to end users and society in general. Although numerous studies have examined the effects of information and communication technologies (ICT) on open data portals, the influence of data dissemination instruments and data governance practices on the quality of data published in open data portals has received less attention. This paper seeks to fill that gap. The analysis is based on survey responses from teams responsible for managing open data in public organisations in Brazilian government data portals. The study reveals that the information dissemination, institutionalisation at the macro level and the support resources of open data programmes influence the quality of published data. These conclusions are of interest to politicians and practitioners involved in raising awareness of the usability of open data portals. Government agencies seeking to stimulate development should consider improving open data governance practices and increasing user awareness of their availability to promote user engagement.